The Effect of School Policy on Bullying in Elementary Schools - Ningrum, Anisa Kumala; Senowarsito, Senowarsito; Murniati, Ngurah Ayu Nyoman (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study aims to examine the influence of school policy on bullying in elementary schools in Tembalang District, Semarang City. The study used a quantitative approach with a survey method through an ex post facto correlational design. The research population consisted of 176 elementary school teachers in the Baskara Sumirat Cluster, with a sample of 122 teachers determined using a proportional random sampling technique based on the Slovin formula. Data were collected using a Likert-scale questionnaire covering the dimensions of policy formulation, policy content, policy socialization, and policy implementation, and were then analyzed using simple linear regression. The ANOVA test results showed an F value of 409.731 with a significance level of 0.000 (p<0.05), indicating that school policy has a significant effect on bullying. The regression equation Ŷ = 202.518 − 1.055X₁ shows a negative and significant effect, with an R-Square value of 0.773, meaning that 77.3% of the variation in bullying can be explained by school policy. These findings imply that school policies that are clearer, more consistent, and well socialized can significantly reduce the occurrence of bullying in elementary schools.